Anti-Proliferative Activity of Glucagon-Like Peptide-1 Receptor Agonist on Obesity-Associated Breast Cancer: The Impact on Modulating Adipokines' Expression in Adipocytes and Cancer Cells - Alaa A. Alanteet; Hala A. Attia; Sameerah Shaheen; Musaed Alfayez; Bisher Alshanawani (SAGE Publishing, 2021)
Obesity is associated with high risk and poor prognosis of breast cancer (BC). Obesity promotes BC cells proliferation via modulating the production of adipokines, including adiponectin (anti-neoplastic adipokine), leptin (carcinogenic adipokine) and inflammatory mediators. In the present study we investigated the anti-proliferative effects of liraglutide (LG; anti-diabetic and weight reducing drug) on MCF-7 human BC cells cultured in obese adipose tissue-derived stem cells-conditioned medium (ADSCs-CM) and whether this effect is mediated via modulating the adipokines in ADSCs and cancer cells. Proliferation was investigated using AlamarBlue viability test, colony forming assay and cell cycle analysis. Levels and expression of adipokines and their receptors were assayed using ELISA and RT-PCR. LG caused 48% inhibition of MCF-7 proliferation in obese ADSCs-CM, reduced the colony formation and induced G0/G1 phase arrest. LG also decreased the levels of inflammatory mediators, suppressed the expression of leptin, while increased mRNA levels of adiponectin and their receptors in obese ADSCs and cancer cells cultured in obese ADCSs-CM. In conclusion, LG could mitigate BC cell growth in obese subjects; therefore it could be used for clinical prevention and/or treatment of BC in obese subjects. It may assist to improve treatment outcomes and, reduce the mortality rate in obese patients with BC.